Comparative analysis of clinical signs between persons with confirmed and unfirmed diagnosis of the temporomandibular joint disorders - Макєєв, Валентин Федорович; Телішевська, Оксана Дмитрівна; Михайлевич, Марта Юріївна (Actual Dentistry, 2020)
Resume. The issue of etiology, pathogenesis and diagnosis of temporomandibular disorders (CHD) remains not fully understood and proven. Understanding the etiology of the temporomandibular disorders is extremely important in identifying and eliminating potential pathological factors. The attention of dental practitioners should be drawn to the need to carefully collect a medical history of a potential patient to identify diseases that may provoke the development of SNA on the primary examination of the patient, which may prevent their development or facilitate their course. The goal: to perform a comparative analysis of a number of clinical features between individuals diagnosed with a form of temporomandibular disorder and individuals who have been found to have an imbalance in the TMD or have not been confirmed. Results. It has been determined that such parameters as «unstable occlusion», «front teeth out of contact», «lateral teeth out of contact», «cutting teeth limited», «cutting teeth missing» are percentages in the main group (by subgroups), that in the comparison group are statistically unreliable (p > 0.05), which suggests that the occlusive factor in the development of TMD is not decisive. It should be noted that the test for express imprisonment (Hamburg Protocol), with the right to clinical use, remains only a fully pre-diagnostic tool with possible elements of significant errors as in the establishment of a definitive diagnosis of TMD in the future, and especially in the case of rejection of a definitive diagnosis of TMD. The analysis shows that the complaints of pain in patients in the main group, that in the comparison group are almost identical and this requires the clinician a high degree of awareness of the features of the symptoms of the temporomandibular disorders in their differential diagnosis. Conclusions. It is confirmed that a number of clinical signs inherent in the temporomandibular disorders are alsodetermined in individuals whose diagnosis of TMD is not confirmed at all, or was imitated under TMD. Key words: temporomandibular joint, temporomandibular disorder, diagnosis.